Analysis of Building Renovation Methods and Contemporary Advancements in The Modern Era - Wang, Yuelin (Transactions on Engineering and Technology Research, 2024)
Changes in the primary forms of remodeling and renovation of buildings and the current development of remodeling and renovation of buildings in modern cities. As the pace of urbanization is accelerating, the renovation of old buildings has become a way to change the appearance and cultural geography of the city and to improve the quality of life of its inhabitants. In addition, building renovation can be linked to the modern development trend of sustainable development, and the renovation of buildings can be done in an environmentally friendly way. In this study, a case study of a building lobby and the HSBC Tower in London was conducted. An overview of the current state of building renovation is given. In today's rapidly developing urban environments, building renovation has become a vital design practice, with building renovation and remodeling focusing not only on the form of the building but also on the redefinition of functional, cultural, and social values. Literature on building remodeling and renovation was also systematically reviewed. In these processes, there are two points worth discussing in the study of architectural renovation: whether architectural renovation changes or destroys the cultural value of the building itself and whether economic reasons affect renovation in architectural renovation and retrofitting.